BUDAYA KESELAMATAN KERJA DI INDUSTRI KONSTRUKSI: TINJAUAN DAN USUSLAN PENELITIAN DI MASA DEPAN - Achmad Hidayat Sutawidjaya; Winda Widyanty (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
This article aims to describe the state-of-the-art in occupational safety culture in the construction industry and propose a future research agenda. A systematic literature review is carried out comprehensively about the study of work safety culture in the construction industry in relation to improving employee performance which has an impact on improving company performance. Previous research has shown work safety culture as a corporate culture that can reduce accident rates and improve safety performance, but there is no research that discusses how the role of work safety culture from the employee's point of view can contribute to improving company performance, especially in high-risk industries such as the construction industry. . In addition, previous research has not revealed the interpretation of work safety culture based on the practice of implementing work safety culture at the employee level in construction companies. Based on the review conducted, eight future research agendas were proposed. This article is believed to be the first to discuss a literature review on work safety culture in relation to improving company performance through the perspective of employees in the construction industry in Indonesia. Keywords: construction industry, safety culture, company performance, state-of-the-art, literature review